PENGARUH KERJA SHIFT TERHADAP EFEKTIVITAS KERJA KARYAWAN PT SIGMA AND HEART INDONESIA - Wulan, Sri Ayu Gerana; Haji, Son; Purwanto, Purwanto (Gapenas Publisher, 2025)
This study aims to determine the effect of shift work on employee effectiveness at PT Sigma And Heart Indonesia. The research employs a quantitative approach using simple linear regression analysis and involves 40 respondents who are shift workers. Data were collected through Likert-scale questionnaires. The results indicate that shift work has a positive and significant influence on work effectiveness. This is evidenced by the regression test results showing a significance value of 0.000 (p<0.05) and a t-statistic of 10.138, which is greater than the t-table value of 2.024, with a regression coefficient of 0.818. Additionally, the coefficient of determination (R2) is 0.730, indicating that shift work explains 73% of the variance in employee effectiveness, while the remaining 27% is influenced by other factors outside the study. The research also finds that shift work affects four aspects of work effectiveness: work quantity, work quality, timeliness, and independence. Based on the questionnaire responses from shift employees, including those on permanent night shifts, it was observed that they can maintain a good level of productivity. Therefore, the results suggest that when shift work is organized with a proper shift system, well-structured work schedules, fair scheduling, operational support from management, and employees' ability to adapt and sustain performance under varying working conditions, it can support overall employee effectiveness.